(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The development of foreign economic relations between the Siberian Federal District (SFD) of the Russian Federation and the Kyrgyz Republic (KR) is a strategically important aspect of cooperation, driven by historical, economic, and cultural ties. Rich in natural resources and endowed with a well-developed industrial base, Siberia, and Kyrgyzstan, with its significant agricultural and hydropower potential, have complementary economies, creating favorable conditions for the growth of mutual trade, investment, and collaboration. Key areas of cooperation include agriculture, energy, industrial production, and transport-logistics infrastructure. A crucial aspect is the establishment of efficient transport corridors to improve logistics processes and support the export of agricultural products. In addition, labor migration and the unified labor market of the EAEU play a significant role in strengthening economic ties. Joint projects and research, including those within the framework of international initiatives such as UNIDO, contribute to the long-term development of mutually beneficial regional cooperation.